Predictors and Long-Term Outcome of Ablation of Discrete Pre-potentials in Patients With Idiopathic Ventricular Arrhythmias Originating From the Aortic Sinuses of Valsalva - Wei, Hui-Qiang; Guo, Xiao-Gang; Zhou, Gong-Bu; Sun, Qi; Yang, Jian-Du; Xie, Hai-Yang; Liang, Jackson; Zhang, Shu; Wu, Shulin; Ma, Jian (Frontiers in Cardiovascular Medicine, 2021)
Background: The predictability and long-term outcome of the discrete pre-potential (DPP) of idiopathic ventricular arrhythmias (VAs) arising from the aortic sinuses of Valsalva (ASV) have not been fully identified. Methods: Of 687 consecutive patients undergoing ablation of outflow tract VAs, there were 105 (15.3%) patients with VAs originating from the ASV region who were included. Detailed mapping was performed within the ASV in all patients. Electrocardiographic, electrophysiological parameters, and long-term success rate were compared between patients with and without the DPPs. Results: A DPP was recorded in 67 of 105 (63.8%) patients, including 38 left sinus of Valsalva (LSV)-VAs (38/105, 36.2%) and 29 right sinus of Valsalva (RSV)-VAs (29/105, 27.6%). The patients with DPPs had wider QRS duration (152 ± 17 vs. 145 ± 14 ms, p < 0.001). The average of earliest activation time was significantly earlier in patients with DPPs (−38.6 ± 8.5 vs. −27.7 ± 5.7 ms, p < 0.001). Mean time from the first lesion to elimination of VAs was shorter in patients with DPPs (2.3 ± 2.1 s vs. 4.9 ± 1.0 s, p < 0.001). A stepwise logistic multivariable analysis identified only younger age as a significant predictor of DPP (age ≤ 35.5 years predicted DPP with 92.9% positive predictive value). During a follow-up duration of 42.5 ± 22.3 months, 63 (94.0%) patients with DPPs and 30 (78.9%) patients without DPPs remained free of recurrent VAs (p = 0.027). Conclusion: Discrete pre-potentials were observed in 63.8% of patients with VAs arising from the ASV. Ablation in patients with DPPs was associated with higher long-term success. DPPs were seen more commonly in younger (age ≤ 35.5 years) patients.